IMPLEMENTASI KEBIJAKAN MAJALENGKA RAHARJA QUICK RESPONSE BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK TERHADAP MASYARAKAT (STUDI DESKRIPTIF DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MAJALENGKA) - Cika Tesazabalia, - (2020)
ABSTRACT CIKA TESAZABALIA. (1601243). IMPLEMENTATION OF MAJAENGKA POLICY OF QUICK RESPONSE RAHARJA BASED ON INFORMATION TECHNOLOGY IN IMPROVING THE QUALITY OF PUBLIC SERVICES TOWARD COMMUNITIES This research is motivated by the development of increasingly sophisticated information technology that can be utilized by the government in communicating directly with the public. Limited public information, complaints that are often not handled optimally, ignorance of the public in submitting complaints and aspirations as well as lengthy and convoluted administration resulted in the services provided are not satisfying the community. Through the Majalengka Raharja Quick Response policy, it is expected to be the main solution in improving the quality of public services in Majalengka Regency. This policy can certainly be a regional innovation in serving and handling various complaints, complaints and aspirations of the public regarding public services. The purpose of this study was to determine and analyze the implementation of Majalengka Raharja Quick Response policies in improving the quality of public services. This research uses a qualitative approach and descriptive method. Data collection techniques carried out in this study through interviews, observation, documentation, literature studies, and data analysis techniques by data reduction, data presentation, drawing conclusions and verification as well as conducting data validity. The results showed that (1) based on five dimensions of public service quality, four of them had met service indicators including reliability, responsiveness, assurance and empathy. Whereas the dimension of physical evidence still has shortcomings in terms of maintaining facilities and infrastructure as policy support. (2) the obstacles faced in implementing the Majalengka Raharja Quick Response policy are blankspots, large budgets, limited number of daily field workers and lack of socialization regarding service programs. (3) efforts undertaken by Diskominfo are to build a Base Transceiver Station, procure infrastructure facilities, re-recruit the number of daily field staff members and carry out large-scale socialization covering the entire territory of Majalengka Regency. Keywords: Policy, Information Technology, Service Quality